A Critical Evaluation of the Twelfth Grade English Language Textbook for Afghanistan High Schools - Rahim, Mohammad Naim; Mohammadi, Tawos; Hashemi, Aminuddin (Elsya : Journal of English Language Studies, 2021)
Since textbook evaluation is a prominent task for educational development, hence, the study is motivated to extend the ideas towards the best of English as a foreign language teaching in high schools. Globally, the English language is taught aligned with 21st century skills, yet textbooks are lacking some of these skills and approaches in Afghanistan. Therefore, the study applied a mixed-method to critically evaluate the 12th grade English language textbook of high schools in Afghanistan. The data is collected using an adopted textbook evaluation checklist and a Likert-Scale ranging from “Poor” to “Excellent”. Content analysis is used to interpret and describe the meaning qualitatively from the number scale of the item in the checklist. Likert-Scale is also analyzed separately through SPSS. The results show that the aims of the course did not correspond closely to the aims of the teaching program and the needs of the learners in the textbook. However, the layout of the textbook is clear, and the students can find their way if an individual study is intended. In terms of the skills, the textbook stated that it covers all four skills of language learning, but the evaluation indicates a considerable focus on reading, grammar, and vocabulary. In conclusion, the study highlighted that the textbook requires to be updated to be focusing more on topic contents related to the needed skills and to make it more user-friendly. This contributes to promoting textbook development in the Ministry of Education and provides an in-depth understanding of the current status of the available textbooks in the high schools of Afghanistan.